2019
DOI: 10.1063/1.5055684
|View full text |Cite
|
Sign up to set email alerts
|

Chemical signatures of surface microheterogeneity on liquid mixtures

Abstract: Many chemical reactions in Nature, the laboratory, and chemical industry occur in solvent mixtures that bring together species of dissimilar solubilities. Solvent mixtures are visually homogeneous, but are not randomly mixed at the molecular scale. In the allimportant binary water-hydrotrope mixtures, small-angle neutron and dynamic light scattering experiments reveal the existence of short-lived (<50 ps), short-ranged (∼1 nm) concentration fluctuations. The presence of hydrophobic solutes stabilizes and exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(42 citation statements)
references
References 109 publications
0
42
0
Order By: Relevance
“…Although the flow of β-caryophyllene molecules injected into the spraying chamber in this case was much larger than in the first set of experiments, product signals remained within background noise ( Figure S2, Reference 26). 26 We inferred that most if not all of the FC and HH products we observed were produced on the surface of intact liquid microjets rather than on microdroplets or in the gas-phase. Similar experiments on the protonation of isoprene on acidic water, in which we tested the effect on product signals of the relative distance between the isoprene gas streams and the tip of the nebulizer, led to the same conclusion.…”
Section: Products Of Gas-liquid Reactions Are Formed On Liquid Microjmentioning
confidence: 81%
See 2 more Smart Citations
“…Although the flow of β-caryophyllene molecules injected into the spraying chamber in this case was much larger than in the first set of experiments, product signals remained within background noise ( Figure S2, Reference 26). 26 We inferred that most if not all of the FC and HH products we observed were produced on the surface of intact liquid microjets rather than on microdroplets or in the gas-phase. Similar experiments on the protonation of isoprene on acidic water, in which we tested the effect on product signals of the relative distance between the isoprene gas streams and the tip of the nebulizer, led to the same conclusion.…”
Section: Products Of Gas-liquid Reactions Are Formed On Liquid Microjmentioning
confidence: 81%
“…[31][32] More direct evidence was obtained from the dependence of the FC and HH (see entry 4, above) products signal intensities in the ozonolysis of β-caryophyllene as functions of the applied polarizing voltage. 26 It was found that both signal intensities strictly increased (with a correlation coefficient ρ 2 = 0.99) with the square root of the polarizing voltage V ½ (see Figure S3 of Reference 26). 26 We inferred the signature of a purely kinematic effect on the trajectories of charged microdroplets in the spraying chamber, rather than electric field effects on chemistry.…”
Section: Applied Electric Fields Deflect Charged Microdroplets But Domentioning
confidence: 96%
See 1 more Smart Citation
“…Since microheterogeneity should be a general phenomenon in "internally mixed" aqueous organic mixtures, we suggest that the existence of inhomogeneities at the molecular level, as distinct from mesoscopic segregation, [63][64][65] could play unanticipated roles in atmospheric aqueous media. 56 The relatively short lifetimes of the -HHs derived from the ozonolysis of monoterpenes relative to the dramatic persistence of the -HH derived from -Tp (Table and Fig a  1/e = 1/k 1 catalyzed reaction. This is an important effect, considering that ambient cloud water and aqueous aerosols are more acidic than previously assumed.…”
Section: Table 1-rate Coefficients Of -Hhs Decay In Water:acetonitrimentioning
confidence: 99%
“…This new type of "weak" (judging by the magnitude of the interaction energy, which does not exceed k B T [17]), but the extremely effective and spontaneous structuring of liquids has not attracted the attention of researchers for a long time. Only recently has its importance been identified for an adequate description of reactions and other chemical processes [8,9,13,14,[18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%